Mineralization of electronic wastewater by electro-Fenton with an enhanced graphene-based gas diffusion cathode. (20th June 2018) - Garcia-Rodriguez, Orlando; Lee, Yi Yang; Olvera-Vargas, Hugo; Deng, Fengxia; Wang, Zuxin; Lefebvre, Olivier
Abstract: In recent years, electro-Fenton (EF) has emerged as a promising solution for the mineralization of refractory organic compounds. Within the different electrodes used in EF, gas diffusion electrodes (GDEs) are among the most efficient in achieving high mineralization of pollutants. In this study, carbon cloth (treated with polytetrafluoroethylene) GDE (PTFE-CC-GDE) was coated for the first time with electrochemically exfoliated graphene in order to improve the generation of H2 O2 and thus the mineralization of real industrial electronics wastewater by EF. Remarkably, the graphene-coated GDE allowed reaching H2 O2 concentrations as high as 495 mg L −1 (specific H2 O2 production of 28 mg cm −2 ). As a result, over 80% of mineralization of electronics wastewater was achieved following 180 min of EF under the optimum operating conditions (29 mA cm −2, 0.2 mM of Fe 2+ and 0.2 L min −1 air flow). In conclusion, this study demonstrated the great capacity of the graphene-coated GDE for H2 O2 production enhancement and its potential for the treatment of real industrial wastewater by EF.